2022
DOI: 10.6004/jnccn.2022.7049
|View full text |Cite
|
Sign up to set email alerts
|

Change Toward Healthier Lifestyles Is Associated With Better Health-Related Quality of Life in Long-Term Colorectal Cancer Survivors

Abstract: Background: Little is known about how changes in a constellation of lifestyle factors affect health-related quality of life (HRQoL) in colorectal cancer (CRC) survivors. Our study aimed to investigate the association between changes in healthy lifestyle and HRQoL over time in survivors of stage I–IV CRC. Methods: We included 2,283 long-term (≥5 years postdiagnosis) survivors. A healthy lifestyle score (HLS) comprising smoking, alcohol consumption, diet, physical activity, and body fatness was derived at diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Much of the previous research in this area has been cross‐sectional in nature, apart from a recent series of articles by Kenkhuis et al exploring longitudinal relationships among colorectal cancer survivors' post‐treatment adherence with WCRF and QoL, 27,28,57 which suggests that higher MVPA was longitudinally associated with higher QoL 28 . Furthermore, Eyl‐Armbruster et al found that positive changes in lifestyle behaviours (composite score) among colorectal cancer survivors' from baseline to 5 years was associated with better functioning and lower symptom burden at 5 years follow‐up 58 . Future prospective studies should seek to better understand the direction of these relationships in different groups of cancer survivors, and intervention studies should aim to explore whether adhering to these recommendations results in better patient QoL outcomes in the longer term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the previous research in this area has been cross‐sectional in nature, apart from a recent series of articles by Kenkhuis et al exploring longitudinal relationships among colorectal cancer survivors' post‐treatment adherence with WCRF and QoL, 27,28,57 which suggests that higher MVPA was longitudinally associated with higher QoL 28 . Furthermore, Eyl‐Armbruster et al found that positive changes in lifestyle behaviours (composite score) among colorectal cancer survivors' from baseline to 5 years was associated with better functioning and lower symptom burden at 5 years follow‐up 58 . Future prospective studies should seek to better understand the direction of these relationships in different groups of cancer survivors, and intervention studies should aim to explore whether adhering to these recommendations results in better patient QoL outcomes in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Furthermore, Eyl‐Armbruster et al found that positive changes in lifestyle behaviours (composite score) among colorectal cancer survivors' from baseline to 5 years was associated with better functioning and lower symptom burden at 5 years follow‐up. 58 Future prospective studies should seek to better understand the direction of these relationships in different groups of cancer survivors, and intervention studies should aim to explore whether adhering to these recommendations results in better patient QoL outcomes in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the clusters of keywords co-occurrence, as well as the frequency and centrality of keywords into account, the research hotspots in this field were summarized as follows. Firstly, physical activity was a hot topic when exploring the effect of behavior changes on QoL for GI cancer survivors [ 23 , 45 , 46 ]. Moderate to intense PA has been demonstrated to be beneficial in improving the QoL of GI cancer survivors [ 47 , 48 ], but the health benefits of light PA were still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…A study demonstrated that 36 % of I ∼ III CRC survivors experienced moderate to high levels of psychological distress, and after a 2-year follow-up, 13 % of survivors still reported low QoL or high levels of psychological distress [ 57 ]. Besides, women, survivors with lower education levels, and symptoms of fatigue, sleep disorders, and pain were more likely to suffer from high levels of psychological distress [ 57 , 58 ], thus it is necessary to strengthen the health education [ 59 ] and lifestyle interventions [ 46 , 60 ] for them. On the other hand, the association between psychological distress and QoL was also a hot research direction.…”
Section: Discussionmentioning
confidence: 99%
“…Shi and In conclusion, studies included in this Research Topic underscore the complex relationship between health-promoting and health-risk behaviors in shaping individuals' health trajectories. By shedding light on the intrinsic mechanisms and contextual elements that shape these behaviors, healthcare practitioners and policymakers can craft tailored interventions aimed at encouraging healthier lifestyles and alleviating the burden of preventable illnesses (6). Additionally, the content of this Research Topic could serve as a valuable material for textbooks on health behavior studies.…”
Section: Editorial On the Research Topic Exploring The Interaction Be...mentioning
confidence: 99%